2002
DOI: 10.1210/jcem.87.3.8321
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Body Cell Mass in Cushing’s Syndrome: Effect of Treatment

Abstract: Cushing's syndrome (CS) is associated with low fat-free mass, but it is unclear whether hypercortisolism causes a loss of whole body protein. Body composition was studied prospectively in 15 patients with untreated CS (n = 14 pituitary adenoma; n = 1 adrenal adenoma), in 15 nonobese healthy controls, and in 15 weight-matched obese controls by 3 different methods: total body potassium counting (TBP), bioelectrical impedance analysis (BIA), and anthropometry. In 6 patients, body composition was studied before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
3
26
1
1
Order By: Relevance
“…Our results also indicate that the central obesity associated with long-term hypercortisolism in CS is not completely reversible after treatment. Previous studies on the reversibility of reduced LBM and skeletal muscle mass have demonstrated either unchanged (4,8,9,10) or reduced LBM after treatment (7,11). In our study, after adjustment for various confounders, no difference in skeletal muscle mass was observed between patients and controls.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results also indicate that the central obesity associated with long-term hypercortisolism in CS is not completely reversible after treatment. Previous studies on the reversibility of reduced LBM and skeletal muscle mass have demonstrated either unchanged (4,8,9,10) or reduced LBM after treatment (7,11). In our study, after adjustment for various confounders, no difference in skeletal muscle mass was observed between patients and controls.…”
Section: Discussioncontrasting
confidence: 57%
“…The study also demonstrates that ongoing GC replacement and a common polymorphism in the GC receptor gene are associated with adverse skeletal health in patients with CS in long-term remission. Adipose tissue mass decreases after treatment for CS (4,7,8,9,10), but whether complete normalisation occurs at long-term follow-up is not fully explored. One previous cross-sectional study found an increased total and abdominal fat mass in patients with CS after a mean time of 11 years in remission in comparison with age-, gender-and BMI-matched controls (11).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle damage can persist both short-and long-term after cure. Indeed, the reduced muscle area in the arms showed no relevant improvement 6 months after successful treatment (102). MRI body composition assessment of CD patients 20 months after remission showed that total and limb skeletal muscle is actually reduced compared to active disease (99).…”
Section: Muscle In Csmentioning
confidence: 97%
“…Thus, when in excess, cortisol is an overall catabolic hormone, which decreases lean body mass and muscle mass and may increase energy expenditure (7). At the same time, glucocorticoids increase appetite and food intake (7) and may increase fat mass (8,9). Cortisol also induces insulin resistance (2,3), and it has been proposed that glucocorticoids could contribute to the metabolic syndrome and cardiovascular disease (10,11).…”
mentioning
confidence: 99%